2021
DOI: 10.3390/ma14112797
|View full text |Cite
|
Sign up to set email alerts
|

Pearl Powder—An Emerging Material for Biomedical Applications: A Review

Abstract: Pearl powder is a well-known traditional Chinese medicine for a variety of indications from beauty care to healthcare. While used for over a thousand years, there has yet to be an in-depth understanding and review in this area. The use of pearl powder is particularly growing in the biomedical area with various benefits reported due to the active ingredients within the pearl matrix itself. In this review, we focus on the emerging biomedical applications of pearl powder, touching on applications of pearl powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…44 Prior studies have demonstrated that nacre powder could promote the synthesis of the sialoprotein in jaw osteoblasts, and induce the expression of ALP genes. 26,55 In our study, the ALP-positive area was obviously larger in the NPP-5% groups than those in the other two groups for 7 days (Fig. 7A).…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…44 Prior studies have demonstrated that nacre powder could promote the synthesis of the sialoprotein in jaw osteoblasts, and induce the expression of ALP genes. 26,55 In our study, the ALP-positive area was obviously larger in the NPP-5% groups than those in the other two groups for 7 days (Fig. 7A).…”
Section: Resultssupporting
confidence: 48%
“…In addition, incorporated nacre could gradually release Ca 2+ , inducing osteogenic differentiation of cells through the calcium/calmodulin signaling. 44,55,56 This journal is © Royal Society of Chemistry 20xx…”
Section: Cell Osteogenic Differentiationmentioning
confidence: 99%
“…10 Modern research has confirmed that matrix proteins from pearl hydrolysis also have antioxidant, anti-inflammatory and anti-apoptotic effects. 11,12 However, as a precious medicinal material, pearls are complex to process, less productive and expensive. Pinctada martensii, also known as pearl oyster, is one of the main shellfish species for pearl cultivation in the coastal areas of China.…”
Section: Introductionmentioning
confidence: 99%
“…Pearl powder is commonly used in traditional Chinese medicine for palpitations, insomnia, convulsions, epilepsy, and ulcers for a long history [1,2] . Pearl powder also has been applied to beauty treatment for skin moisturizing and whitening [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Pearl powder is commonly used in traditional Chinese medicine for palpitations, insomnia, convulsions, epilepsy, and ulcers for a long history. [1,2] Pearl powder also has been applied to beauty treatment for skin moisturizing and whitening. [3] Hence, a variety of pearl related products are being produced by different manufactories, especially in the areas of dietary supplements and skin-care.…”
Section: Introductionmentioning
confidence: 99%